1998
DOI: 10.1104/pp.117.1.113
|View full text |Cite
|
Sign up to set email alerts
|

Indole-3-Acetic Acid Controls Cambial Growth in Scots Pine by Positional Signaling1

Abstract: The vascular cambium produces secondary xylem and phloem in plants and is responsible for wood formation in forest trees. In this study we used a microscale mass-spectrometry technique coupled with cryosectioning to visualize the radial concentration gradient of endogenous indole-3-acetic acid (IAA) across the cambial meristem and the differentiating derivatives in Scots pine (Pinus sylvestris L.) trees that had different rates of cambial growth. This approach allowed us to investigate the relationship between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
201
0
4

Year Published

2002
2002
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 283 publications
(218 citation statements)
references
References 25 publications
13
201
0
4
Order By: Relevance
“…Early analyses suggested that SDs could induce the cessation of cambial cell division by reducing cambial auxin levels (28,29). This hypothesis was subsequently rejected, however, when high-resolution MS analysis indicated that no reduction in cambial auxin levels occurred during the activitydormancy cycle (30). These results were surprising, because if cambial auxin levels remain unchanged during growth cessation, what would be the mechanism that inhibits cell division, a process normally promoted by auxin?…”
Section: Discussionmentioning
confidence: 45%
“…Early analyses suggested that SDs could induce the cessation of cambial cell division by reducing cambial auxin levels (28,29). This hypothesis was subsequently rejected, however, when high-resolution MS analysis indicated that no reduction in cambial auxin levels occurred during the activitydormancy cycle (30). These results were surprising, because if cambial auxin levels remain unchanged during growth cessation, what would be the mechanism that inhibits cell division, a process normally promoted by auxin?…”
Section: Discussionmentioning
confidence: 45%
“…All major classes of phytohormones may have important roles in xylogenesis (Aloni et al, 1990;Uggla et al, 1998;Andersson-Gunneras et al, 2006), and therefore could affect both growth and lignin. An integrated genetic, transcriptional, and metabolic approach could provide a systematic path to determine the mechanism of control.…”
Section: Metabolic Regulation Of Lignin Biosynthesismentioning
confidence: 99%
“…On the one hand, the influence of environmental factors, well documented in dendroecology through climate-growth relationships (Schweingruber, 1996), was demonstrated to be complicated by the asynchronous and long lasting production and maturation of xylem cells Fonti et al, 2007;Seo et al, 2008). On the other, the dynamics of wood formation is strongly determined by internal factors, such as cambial age, carbohydrate availability and hormone distribution Uggla et al, 1998;2001). In particular, since the 1960s biologists have been trying to explain (or interpret) the influence of auxin on cambial activity and latewood formation (Aloni 2001;Avery et al, 1937;Denne and Wilson, 1977;Larson, 1969).…”
Section: Introductionmentioning
confidence: 99%
“…Auxin participates in the reactivation of the vascular cambium, inducing the production of xylem and phloem (Larson, 1969) and regulating rate and duration of the developmental processes during xylogenesis (Tuominen et al, 1997;Uggla et al, 1998). Larson's hypothesis affirms that, with the auxin basipetal movement, periclinal divisions in the cambium should also begin at the base of the buds and spread downwards towards the stem (Denne, 1979;Lachaud et al, 1999;Larson, 1969).…”
Section: Introductionmentioning
confidence: 99%